Postmarket Experience of Polymethylmethacrylate–Collagen Gel Dermal Filler. Issue 8 (August 2020) - Lehman, Alayne; Pilcher, Brian; Roberts, Wendy E.; Schlesinger, Todd E.; Vachon, Ginny
Abstract : BACKGROUND: This report synthesizes 12 years of postmarket surveillance data (PMSD) for polymethylmethacrylate (PMMA)–collagen gel dermal filler. OBJECTIVE: To present PMMA–collagen gel PMSD findings on real-world safety. METHODS: Postmarket surveillance data were collected from January 2007 to December 2018 and evaluated to determine the overall adverse event (AE) complaint rate, the nature of reported AEs, and whether the complaint included on-label, off-label, both, or unknown areas. RESULTS: In the 12 years examined, 754, 229 PMMA–collagen gel syringes were distributed worldwide, and 839 product-related complaints (including those classified as unknown) resulted in an overall complaint rate of 0.11%. The 3 most frequent primary complaints in AE reports were lump/bump (309/839, 37%), nodule (152/839, 18%), and swelling (138/839, 16%). Histologically confirmed granuloma accounted for 17/839 complaints (2.0%; overall complaint rate of 0.002%), and histologically unconfirmed granuloma accounted for 66/839 complaints (8%; overall rate of 0.009%). There were 666 complaints representing AEs related to off-label injection in which the periocular area was most frequently represented. CONCLUSION: Although a limiting factor across all PMSD is voluntary reporting and resultant underrepresentation of AEs, the PMSD reported here are consistent with safety findings from US clinical studies in more than 1, 500 patients with up to 5 years of follow-up.